Paediatric radiation oncology in the care of childhood cancer: A position paper by the International Paediatric Radiation Oncology Society (PROS). Issue 2 (May 2016) - Kortmann, Rolf-Dieter; Freeman, Carolyn; Marcus, Karen; Claude, Line; Dieckmann, Karin; Halperin, Edward; Esiashvili, Natia; Paulino, Arnold; Mahajan, Anita; Seiersen, Klaus; Ahern, Verity; Ricardi, Umberto; et al.
Abstract: Paediatric malignancies are a challenge for the radiation oncologist due to their rarity, the great variety of histological types, and the complexity of treatment concepts that evolve over time. The Paediatric Radiation Oncology Society (PROS) is the only internationally operating society for paediatric radiation oncology. The objectives of PROS are to set a world-wide standard of excellence with respect to radiation oncology aspects in curing children and adolescents with cancer, to provide a forum for communication between radiation oncologists, and to exchange information with all professionals involved in the management of paediatric and adolescent cancer. Challenges include the need to promote education and support practice in low and middle income countries (LMIC) as well as the cost and availability of modern treatment technologies for all but most especially these countries. Collaborations with other societies that include for example the education programmes provided jointly with ESTRO, and the upgraded technical platform of the PROS web site offer new possibilities to enhance the efficacy of PROS in education and support of paediatric radiation oncology practice world-wide. PROS has made an important contribution to the management of childhood malignancies over the past decade and new and developing collaborations between PROS and other societies or organizations will ultimately lead to a reduction in world-wide health care inequalities.